2011
DOI: 10.3892/or.2011.1293
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial cells of Cajal (ICC)-like-c-Kit positive cells are involved in gastritis and carcinogenesis in human stomach

Abstract: Dense fusiform cell bodies with many processes were found in each layer. We also studied the c-Kit-positive immunoreactivity distribution pattern in the mucosa. c-Kit (+) cells were found mainly around the epithelial repair zone of the normal gastric fundus/corpus and of the fundus/corpus with non-metaplastic chronic gastritis. Notably, they were found attached to the epithelia of the repair zone in non-metaplastic chronic gastritis. In chronic gastritis with intestinal metaplasia, they were found scattered ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In our previous study, in fact, we reported activation of the NO/sGC pathways in high K + -induced relaxation in longitudinal smooth muscle of the human gastric corpus and fundus [ 10 , 11 ]. It has also been reported that interstitial cells of Cajal (ICC) express NO-sensitive sGC and it is the primary target of NO released from nNOS neurons even in human stomach [ 13 , 29 , 30 , 31 , 32 , 33 ]. Because NO signals are transmitted to smooth muscle of the GI tract and ICC in human stomach was already reported, a NO-mediated pathway may be responsible for histamine-induced relaxation in the human stomach [ 13 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, in fact, we reported activation of the NO/sGC pathways in high K + -induced relaxation in longitudinal smooth muscle of the human gastric corpus and fundus [ 10 , 11 ]. It has also been reported that interstitial cells of Cajal (ICC) express NO-sensitive sGC and it is the primary target of NO released from nNOS neurons even in human stomach [ 13 , 29 , 30 , 31 , 32 , 33 ]. Because NO signals are transmitted to smooth muscle of the GI tract and ICC in human stomach was already reported, a NO-mediated pathway may be responsible for histamine-induced relaxation in the human stomach [ 13 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several layers of muscle are found in the human stomach [19,20]. Circular and longitudinal muscle is regulated by the coordination of slow waves [21].…”
Section: Discussionmentioning
confidence: 99%
“…Negative controls were performed by omitting the primary antibodies or by substitution them with a non-immune serum in orderto check the specificity of the immunostaining. All sections for histologic and immunohistochemical analysis were examined using a microscope (BX50; Olympus Corporation) and images were captured with an attached camera (ProgRes C14; Jenoptik, Jena, Germany) operated with CapturePro software (Jenoptik) [25,26]. …”
Section: Methodsmentioning
confidence: 99%